2009
DOI: 10.30843/nzpp.2009.62.4810
|View full text |Cite
|
Sign up to set email alerts
|

Ryegrass (<i>Lolium perenne</i>) seed yield response to fungicides a summary of 12 years of field research

Abstract: A summary of seed yield data from 19 fungicide trials in perennial and hybrid ryegrass (Lolium spp) seed crops conducted over a 12 year period is presented Seed yields from the best fungicide treatments were increased on average by 25 in forage ryegrass (390 kg/ha) and 42 in turf ryegrass (580 kg/ha) Seed yield increases were associated with the control of stem rust and/or maintaining green leaf area during seed fill In turf ryegrass (susceptible to stem rust) delaying the first fungicide application until ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In the case of perennial ryegrass, the use of fungicides is an equally important element, as many fungal diseases can lead to high crop losses [20]. Studies have shown that the application of fungicides is economically profitable and that an increase in the yield of perennial ryegrass seeds resulting from their application is in the range of 180-920 kg•ha −1 [21].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of perennial ryegrass, the use of fungicides is an equally important element, as many fungal diseases can lead to high crop losses [20]. Studies have shown that the application of fungicides is economically profitable and that an increase in the yield of perennial ryegrass seeds resulting from their application is in the range of 180-920 kg•ha −1 [21].…”
Section: Introductionmentioning
confidence: 99%